10.3k views
3 votes
Factor the trigonometric expression and simplify:1-sin^3x

User Psmith
by
4.4k points

1 Answer

5 votes

Remember the following rule for factoring a difference of cubes:


a^3-b^3=(a-b)(a^2+ab+b^2)

Notice that 1 is equal to 1^3.

Then, to factor the expression:


1-\sin ^3x

Use the identity above with a=1 and b=sin(x):


\begin{gathered} 1-\sin ^3x=(1-\sin x)(1^2+1\cdot\sin x+\sin ^2x) \\ =(1-\sin x)(1+\sin x+\sin ^2x) \end{gathered}

Therefore, a factored form of the given expression is:


1-\sin ^3x=(1-\sin x)(1+\sin x+\sin ^2x)

User Squv
by
4.0k points